The Effectiveness of Independent Curriculum Implementation in SMA Negeri 5 Rejang Lebong: A CIPP-Based Evaluation - Aris Dianto; Hamengkubuwono Hamengkubuwono; Irwan Fathurrochman (Tarbawi: Jurnal Keilmuan Manajemen Pendidikan, 2024)
This study evaluates the implementation of the Independent Curriculum at SMA Negeri 5 Rejang Lebong using the CIPP (Context, Input, Process, and Product) evaluation model. A qualitative evaluative research approach was employed, with data collected through direct observation, in-depth interviews, and document analysis. The findings reveal that: (1) The context evaluation indicates that the school's Operational Curriculum (KOSP) aligns with established standards. (2) The input evaluation highlights that infrastructure does not fully meet standards, teachers demonstrate strong academic, personal, and social competencies but lack professional competence, students exhibit readiness for learning but limited engagement, and the availability of teaching modules remains insufficient. (3) The process evaluation shows that interactive and engaging learning environments meet expectations, yet inspirational and student-motivating aspects, as well as teachers’ roles in guidance and facilitation, are not fully realized. Assessment and reflection processes comply with the standards, and the implementation of the P5 (Strengthening Pancasila Student Profile) project meets the required criteria. (4) The product evaluation reveals that students' academic reports do not meet the expected standards, whereas P5 reports comply. These findings underscore the need for enhanced infrastructure, teacher professional development, and comprehensive curriculum evaluation to ensure the Independent Curriculum’s effectiveness..